Green Marketing: a Modern Marketing Tool For Sustainable Development: Exploring the Concept and Challenges of Green Marketing for Sustainable Development (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Green marketing is a phenomenon which has developedparticular important in the modern marketing era and has emerged as animportant concept in India as in other parts of the developing and developedworld, and is seen as an important strategy of facilitating sustainabledevelopment. In this research paper, main emphasis has been made of concept,need and importance of green marketing. The Paper aims at finding out whatactually Green Marketing is all about and how can a business firm be morecompetitive by using green marketing strategies to gain a competitive edge overothers. The paper also examines the present trends of green marketing. It alsodiscusses on challenges of green marketing and concludes that green marketingis something that will continuously grow in practice.